(untitled) (Al-Academy, 2016)
This paper deals with the problem of the mechanics of the operation of cinematography in the development of museum exhibition halls. In the first chapter, the researcher dealt with the problem and presented it to reach the goals and purpose of the research, which was represented in using and developing the methods and mechanisms of the presentation to keep pace with what is happening in the world of technology and access to the presented model to new formula and vision declares aesthetical and cognitive measure, thus the search constitutes an importance in absorbing Scenography dimensions in the theater and moved to the idea of the museum and the development of the display models and using them in drawing and representation of perceptions to a cognitive state of visual scene and convert the Panorama scene to moving images through visual and sound effects.In the second chapter, a theoretical framework, which includes the two papers, and it is the aesthetic dimension of the scenography in the art, and it has been tracking the operation system of the aesthetical dimension of scenography in technical races such as decor and theater and the formation, so from the scenography Museum, cities and architecture to scenography exhibition halls based on the optical vision of the fine art for the perceived world according to vision represent images mentally and cognitively. As well as the paper dealt with the scenography and visual display space between the museum and methods of Panorama. The second paper also dealt with visual display space between the museum and the methods of Panorama.Mechanisms scenographic operation are called in this section in the structure of museums , Panorama and its functioning and beauty.A group of works and methods used in the construction of a visual display were presented. The researcher concluded to indicators and theoretical framework, including the function of Scenographic construction which is an investment and create meanings and the temporal and spatial perceptions cross symbols and vocabulary and bodies constitute aesthetic dimensions and variety of visual formulas. The aesthetic dimension of scenography achieved through calling of raw materials and various techniques in image configuration achieved length and breadth, vertically and horizontally in space and various techniques in the image configuration achieved length and breadth, vertically and horizontally in space.The third chapter is an application of the findings of the researcher to the international experiences and then call Scenography as a aesthetic dimension where the researcher worked a group of samples within the exhibition Museum hall of Natural History and included the theme of Fish and rivers section in which spreading the anthropomorphism , the movement element , the addition and the image. The sample builds background of the place environment in Rawa where the river and along its banks palm scene, and there in the middle of the place there was Naor in materializing form connected with engine makes it in the case of slow rotation to suggest Rawa environment and its Naors, and in the river bank some three-dimensional plants that grow naturally without human intervention ; the reeds represents an embrace between drawn shape and the three –dimension shape which is an element of optical excitement and environment that allows the entry of an expression of holographic Naor, and through its movement the watcher feels the environment and place. The second sample is fish in a river environment at the Natural History Museum Hall.The work based on the simulation of river environment. Through the use of a variety of materials such as pulp , cloth and sand, as the business climate suggests rocks which is a three –dimension model for creating a state of delusion. It has been functioning background of safe animatedly using colored cloth transparent allowed to cross the light gives waves and movements of water sense ; add to this a triangle of the cloth process by invisible vicious air creates vibration and ripples with light element and the sound of water (sound recording).All of this act contributed to the granting of the museum a new perception of technical and aesthetic dimensions of the scenography , across the fish movement which is hanging with aquatic plants (of plastic).The fourth chapter the researcher found results and conclusions of the research, including the dimensions and scenography and its manifestations in the visual work, such offer museums safes interested in natural history museums or cultural or figuration for all this governed by optical format gives the viewer visual pleasure and scientific knowledge. The model in the visual presentation reflects many and varied factors affect and do shapes and contents incubating by it for reporting meanings and evidences ; also it represents investment of scenography mechanisms in display the idea of harmonization and communication between science and art, which contributes to the creation of a scientifically and aesthetically museum at the same time and investment scenography techniques in the development of modes of presentation in Iraqi museums